2019
DOI: 10.1186/s13018-019-1436-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of a dual-mobility cup and cementless triple-taper femoral stem combination in total hip replacement: a multicenter retrospective analysis

Abstract: Background: The separate design concepts of dual-mobility cups and triple-taper femoral stems were developed to improve survivorship following total hip replacement (THR) by reducing instability/dislocation and enabling enhanced fixation. Successful outcomes at over two decades have been reported with earlier-generation devices based on these concepts. The current study aimed to provide the first long-term results with a unique pairing of later-generation dual-mobility cup and triple-taper cementless femoral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Many studies have reported on outcomes of HA-coated stems [1,8,9,28,29], but only a few have reported on outcomes of other coatings. Studies on stems with first plasma-sprayed titanium and then HA coating have reported satisfactory mid-and long-term outcomes [6,[30][31][32], this coating combination may provide stronger biological and mechanical bone fixation compared to only HA coating [6,33,34]. A recent study by Liu et al [35] has shown that a pore size between 50 and 800 μm stimulates bone ingrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported on outcomes of HA-coated stems [1,8,9,28,29], but only a few have reported on outcomes of other coatings. Studies on stems with first plasma-sprayed titanium and then HA coating have reported satisfactory mid-and long-term outcomes [6,[30][31][32], this coating combination may provide stronger biological and mechanical bone fixation compared to only HA coating [6,33,34]. A recent study by Liu et al [35] has shown that a pore size between 50 and 800 μm stimulates bone ingrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Only two other stems have published survival rates. The survival rate for the Polarstem (Smith and Nephew, Inc Watford, UK) at 5 years is reported to be 99.6% and the Avenir stem (Zimmer-Biomet, Warsaw IN, USA) at 7 years is 98.9% [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The mean time from index surgery to those symptomatic failures ranged from 34 to 96 months [ 29 ]. A modern generation of DM-THA has been reported with excellent long-term implant survival (more than 95% at 10-year follow-up) [ 30 ]. Since the main objective for most of the included studies was to compare short-term outcome domains, including dislocation, reoperation, functional score, and mortality, the mean follow-up duration ranged from only 12 to 36 months, which was too short to validate and compare implant survival between DM-THA and HA group.…”
Section: Discussionmentioning
confidence: 99%